1,25(OH)2D3 and dihydrotestosterone interact to regulate proliferation and differentiation of epiphyseal chondrocytes - Krohn, Kathrin; Haffner, Dieter; Hügel, Ulrike; Himmele, Rainer; Klaus, Günter; Mehls, Otto; Schaefer, Franz (Calcified tissue international, 2003)
Growth plate chondrocytes are affected by 1,25(OH)2D3 and androgens, which may critically interact to regulate proliferation and differentiation during the male pubertal growth spurt. We investigated possible interactions of 1,25(OH)2D3 and the non-aromatizable androgen dihydrotestosterone (DHT) in primary chondrocyte cultures from young male rats.